# Math x-int's

How do I algebraically find the x-intercepts for this equation y = x^3 - 3x^2 + 3.

I know I need to plug in y = 0 to solve for x.

x^3 - 3x^2 + 3 = 0

But where do I go from there? I don't think I can factor, and I don't think I can use the quadratic formula.

1. 👍 0
2. 👎 0
3. 👁 64
1. It is actually very simple. To solve an equation of the form:

x^3 + a x^2 + b x + c = 0

First, get rid of the quadratic term
a x^2 using the substitution:

x = y - a/3

This step is analogous to how you solve the quadratic equation when you write it as a perfect square.

In this case we aren't finshed yet as the equation now is of the form:

y^3 + p y + q = 0

How do we solve this equation?

Consider the identity:

(a+b)^3 = a^3 + 3a^2b + 3ab^2 + b^3

We can rewrite the right hand side as follows:

a^3 + 3a^2b + 3ab^2 + b^3 =

a^3 + b^3 + 3ab(a+b)

So, we have:

(a+b)^3 = 3ab(a+b)+ a^3 + b^3 ---->

(a+b)^3 - 3ab(a+b) - [a^3+b^3] = 0

Of course, this equation is always satisfied whatever values for a and b you substitute in it. Now, if we choose a and b such that:

3ab = -p (1)

a^3 + b^3 = -q (2)

Then:

(a+b)^3 +p(a+b) + q = 0

so y = a + b is then the solution we are looking for.

So, it all boils down to solving equations (1) and (2) for a and b.

If you thake the third power of (1):

27 a^3b^3 = -p^3

So, if we put A = a^3 and B = B^3, we have:

A*B = -p^3/27

A + B = -q

If you eliminate, say, B , you get a quadratic equation for A which you know how to solve. You then only need to pay attention when you extract the cube roots to find a and b. Equation (1) has to be satisfied, which means that if you choose one of the three possible complex cube roots for A, the root for B is fixed.

1. 👍 0
2. 👎 0
2. So, let's see how this works out for in your case:

x^3 - 3x^2 + 3 = 0

We put x = y + 1, which gives after some simple algebra:

y^3 - 3y + 1 = 0

So, p = -3 and q = 1

We need to solve:

A*B = -p^3/27 = 1

A + B = -q = -1

The second equation says that
B = -(1+A)

Substituting in the first gives:

-A^2 - A = 1 --->

A^2 + A + 1 = 0 ----->

A = -1/2 ± i sqrt[3]/2

We have two solutions because interchanging A and B will give you another solution. But if you do that the other solution for A will be the first solution for B. So we can take:

A = -1/2 + i sqrt[3]/2

B = -1/2 - i sqrt[3]/2

We can rewrite this as:

A = cos(4 pi/3) - i sin(4 pi/3)

B = cos(4 pi/3) + i sin(4 pi/3)

Which we can also write as:

A = exp(-4 pi i/3)

B = exp(4 pi i/3)

Which means that:

a = exp(-4 pi i/9 + 2 pi i n/3)

b = exp(4 pi i/9 - 2 pi i n/3)

Note that the product of a and b must be 1, the integer n which selects which of the three complex cube roots we choose for A fixes the cube root for B.

The solution is thus:

y = a + b =

exp(-4 pi i/9 + 2 pi i n/3)

+ exp(4 pi i/9 - 2 pi i n/3) =

2 cos(4 pi/9 + 2 pi n/3)

And

x = y + 1 = 2 cos(4 pi/9 + 2 pi n/3)

The three solutions are thus:

x = 2 cos(4 pi/9) + 1

x = 2 cos(10 pi/9) + 1

x = 2 cos(2 pi/9) + 1

1. 👍 0
2. 👎 0
3. I guess we will have to find one of the roots by brute force.
We are looking for zeros of f(x) for some x
Make a table to try to find the zeros
for example
x f(x)
0 +3
1 +1
2 -1
3 +3
That is interesting, f(x) goes through zero at least once between x = +1 and x +2. Try x = 1.3
1.3 +1.27
1.4 -.136
Oh, so between 1.3 and 1.4
Try 1.33
1.33 +.045937
1.34 +.019304
1.35 -.007125
Humm, I am not going do go any further. That is close enough for now. The function crosses the x axis at x is about 1.35
Now what. I need to factor that root out so I am left with a quadratic or else continue graphing and calculating to find the other two roots.
To factor it out, note that (x-1.35) is a factor (to our level of approximation) so
(x-1.35)(a x^2 + b x +c) = x^3-3x^2+3
so we need to divide the right by (x-1.35)
I get
x^2 - 1.65 x - 2.2275
solve that quadratic to find the other two roots.
However I bet the problem is a typo unless you have covered this stuff in class.

1. 👍 0
2. 👎 0
posted by Damon
4. Wow... that's a long process. Thanks for the help!

1. 👍 0
2. 👎 0
posted by jeff
5. ivjlllllllllllllllllllllllllllllhjjjjjjlhlh

1. 👍 0
2. 👎 0

## Similar Questions

1. ### math

Hi! I really need help with this question. Please help me. Thanks! If f(x)=6cosx-1, algebraically determine algebraically the x intercepts to the nearest tenth. On the domain x E R.

asked by Katie on April 18, 2009
2. ### Algebra

For the given equation, list the intercepts and test for symmetry. 2+y-121=0 Show tests algebraically

asked by Emily on April 19, 2013
3. ### match

1. Find the x- and y-intercepts algebraically, showing all work for: y = –(2/3)x + 30

asked by Darcy on November 2, 2010
4. ### pre-calculus

R(x)=x^2+x-6 ________ x-3 1. find the domain and y-intercepts 2. find the x-intercepts 3. find the real solution of the equation 4. find the horizontal or oblique asymptotes 5. find the x-axis 6. plot the points

5. ### Algebra

Here's the question I'm having trouble with: Tell how you would identify the intercepts for the graph of the equation: 3x + 6y = 18 I'm not exactly sure how you would find the intercepts from this equation. Thanks!

asked by Celina on December 18, 2008
6. ### Math (pre-celc 12)

Solve this algebraically for the exact values (Meaning find the x-intercepts): (1/x)=x/(3x+18) I'm not sure what to write as the common denominator. I thought it was: 4x+18 because (3x+x+18)=(4x+18), but I'm not sure what to do

asked by Jana on May 17, 2016
7. ### algebra

please show work Find the average rate of change for the given function on the given interval. 3. f(x)=x2-4x; -2 ≤x≤ 4 4. f(x)=2x-1; [0, 3] Find a Point-Slope equation for a line containing the given point and having the given

asked by meme god on November 13, 2017
8. ### Math

If a graph of a quadratic function can have 0, 1 or 2 x-intercepts. How can you predict the number of x-intercepts without drawing the graph or (completely) solving the related equation? Suppose that the graph of f(x) = ax^2+bx+c

asked by Molly on June 4, 2015